Charitable giving and intermediation - Nadine Chlaß; Lata Gangadharan; Kristy Jones (Friedrich Schiller University Jena, 2015)
Charitable donations are often made through intermediaries who can fund themselves from these same donations. Donors who purchase charitable output through an intermediary incur a principal-agent problem with unobservable prices. We compare charitable giving in an experiment with and without intermediation. Different donor types emerge: 41 per-cent of all donors reduce their donation in response to intermediation, 59 per-cent of all donors give as much or more with than without intermediation. The price of charitable output does not explain these types and appears to only matter after taking characteristics of donors moral judgement into account.
Keywords: C91; D64; L31; 330; altruism; charitable giving; charitable institutions; intermediation; moral judgement reasoning; price elasticity